Pesticide Residues In Pond Water Samples From Coastal Area Of Bangladesh - Uddin, M Amin; Chowdhury, MAZ; Rahman, MA; Rashid, MH; Alam, MK (Journal of the Asiatic Society of Bangladesh, Science, 2014)
Water samples collected from twenty five ponds of coastal area were analyzed by HPLC for the presence of organophosphorus, pyrethroid and carbamate pesticide residues. The results reflected slight contamination of some of the water samples with residues of diazinon, chlorpyriphos (organophosphorus insecticide), carbaryl and carbofuran (carbamate insecticide). The concentration of diazinon and chlorpyriphos ranged from 2.31 jig/L to 5.60 pg/L and 0.0 to 3.80 pg/L respectively. Among carbamate pesticides, carbofuran identified in two samples, ranging from 1.40 to 3.71pg/L, carbaryl was detected in two of the samples which ranged from 1.32 to 6.40pg/L, and pyrethroid (cypermethrin) was not detected in any of the samples. However, the residue level was also within the acceptable ranges according to the WHO guideline value (1993) of water quality. But, its presence in surface water as WHO-recommended limits is a matter of concern. In Bangladesh consumption ofpes::c.Jcs has been increased with the introduction of high yielding varieties of rice in recent years But. the widei> cultivated high yielding variety is highly vulnerable to pests and diseases, and 40; : of the crop loss can be attributed to attack by pests and insects in Bangladesh which is a significant loss (Bagchi, et al. 2008). So, the use of pesticide is now an integral part of agriculture for pest control. More than 100 species of insects, 600 weed species. 1500 plant diseases and 1500 species of nematodes are being controlled by pesticide (Brady 1990). As a result, the production of improved variety of rice has significantly increased in recent years. Although pesticide is beneficial for pest control, it also poses a harmful effect to our environment such as the pollution of surface and ground water. After application of pesticide in the crop field it is degraded in the soil by the soil microorganism to some extent but many of the toxic pesticides are transported into surface and ground water by agricultural run off rain water from the crop field. Ultimately, the surface and ground water may be highly contaminated due to this agricultural run off pesticide (Bagchi, et al. 2008). Asiat. Soc. Bangladesh, Sci. 40(2): 319-323, December 2014